The Building a Legal Culture of Awareness in Nitikan Village, Magetan District - Denny Suwondo; Andri Winjaya Laksana; Arpangi Arpangi (LAW FACULTY UNISSULA, 2023)
The Legal awareness of the community in Nitikan Village, Plaosan Subdistrict, Magetan Regency, East Java in particular, needs to be conveyed and information about the law or legislation to the community, in order to increase legal awareness in the community. The purpose of this research is to find out how the Law Awareness Village Community Development of Nitikan Village, Magetan Regency and to analyze the legal awareness of the community in Nitikan Village, Magetan Regency. This type of research is a juridical sociological approach, the method of juridical sociological approach is an approach method that describes a statement that exists in the research field based on legal principles, legal rules, on applicable legislation and has to do with the problems studied. The people of Nitikan Village do not know about the actions that are not permitted or about the penalties for using social media. There are still students who use social media to bully and use impolite words, which shows the lack of legal awareness of the community in using social media wisely. The high level of legal awareness in an area will lead to a civilized society. The community in Nitikan Village, Magetan Regency needs to be given a discourse related to trusted information provider sites and sites that should be avoided. Examining viral news and hoax information that is widely circulated in the community.